Pelvic floor muscle strength in primiparous women according to the delivery type: cross-sectional study - Edilaine de Paula Batista Mendes; Sonia Maria Junqueira Vasconcellos de Oliveira; Adriana de Souza Caroci; Adriana Amorim Francisco; Sheyla Guimaraes Oliveira; Renata Luana da Silva
ABSTRACT Objectives: to compare the pelvic floor muscle strength in primiparous women after normal birth and cesarean section, related to the socio-demographic characteristics, nutritional status, dyspareunia, urinary incontinence, perineal exercise in pregnancy, perineal condition and weight of the newborn. Methods: this was a cross-sectional study conducted after 50 - 70 postpartum days, with 24 primiparous women who underwent cesarean delivery and 72 who had a normal birth. The 9301 PeritronTM was used for analysis of muscle strength. The mean muscle strength was compared between the groups by two-way analysis of variance. Results: the pelvic floor muscle strength was 24.0 cmH2O (±16.2) and 25.4 cmH2O (±14.7) in postpartum primiparous women after normal birth and cesarean section, respectively, with no significant difference. The muscular strength was greater in postpartum women with ≥ 12 years of study (42.0 ±26.3 versus 14.6 ±7.7 cmH2O; p= 0.036) and in those who performed perineal exercises (42.6±25.4 11.8±4.9 vs. cmH2O; p = 0.010), compared to caesarean. There was no difference in muscle strength according to delivery type regarding nutritional status, dyspareunia, urinary incontinence, perineal condition or newborn weight. Conclusion: pelvic floor muscle strength does not differ between primiparous women based on the type of delivery. Postpartum women with normal births, with higher education who performed perineal exercise during pregnancy showed greater muscle strength.